Mixed planting of subtropical Chinese fir in South China improves microbial carbon source metabolism and functional diversity through the accumulation of nutrients from soil aggregates - Deng, Jiazhen; Hu, Jingda; Huang, Yongzhen; Wang, Shengqiang; Ye, Shaoming (Frontiers in Microbiology, 2024)
Abstract Soil microbial functional traits are key indicators of soil microbial ecological traits; however, how mixing patterns of Chinese fir and broadleaved trees drive soil microbial functional trait variation at the aggregate scale and how soil microbial functional traits are linked to soil fertility factors have largely not been determined. In this study, soil from the 0-20 cm depths in three Chinese fir plantations was collected, and the soil samples were separated into >2 mm (large macro-aggregate), 0.25-2 mm (macro-aggregate) and <0.25 mm (micro-aggregate) by complying with an optimal moisture sieving procedure. The metabolic activities, functional diversity and different carbon sources utilization characteristics of the soil microorganisms were determined by the Biolog Eco microplate method. In all Chinese fir plantations, micro-aggregates(<0.25 mm) consistently exhibited the highest levels of microbial metabolic activity, a more uniform carbon source utilisation capacity, and the highest microbial diversity. Micro-aggregates also showed elevated levels of soil organic carbon (OC), total nitrogen (TN), total phosphorus (TP), and higher ratios of C/N and C/P compared to large macro-aggregates and macro-aggregates, indicating that micro-aggregates contain more resources available to soil microorganisms. Soil OC, TN, and TP content were enhanced by integration with Michelia macclurei, suggesting that this combination promotes relatively favourable soil conditions for microbial growth and multiplication. This, in turn, promotes microbial metabolic activity. Furthermore, redundancy and correlation analyses showed that soil OC, TN, and TP were identified as principal determinants of soil microbial functional properties in Chinese fir plantations. In summary, mixed cultivation and aggregate size influenced microbial functional properties via soil nutrient alterations. Consequently, adopting a mixed cultivation approach of Chinese fir and broadleaved trees is advocated in the subtropical regions of Guangxi. Employing a diversity of tree species, including M. macclurei, is recommended for optimal soil quality preservation.